Mild Behavioral Impairment Is Associated With Atrophy of Entorhinal Cortex and Hippocampus in a Memory Clinic Cohort - Matuskova, Veronika; Ismail, Zahinoor; Nikolai, Tomas; Markova, Hana; Cechova, Katerina; Nedelska, Zuzana; Laczó, Jan; Wang, Meng; Hort, Jakub; Vyhnalek, Martin (Frontiers in Aging Neuroscience, 2021)
Objectives: Mild behavioral impairment (MBI) is a syndrome describing late-onset persistent neuropsychiatric symptoms (NPS) in non-demented older adults. Few studies to date have investigated associations of MBI with structural brain changes. Our aim was to explore structural correlates of NPS in a non-demented memory clinic sample using the Mild Behavioral Impairment Checklist (MBI-C) that has been developed to measure MBI. Methods: 116 non-demented older adults from the Czech Brain Aging Study with subjective cognitive concerns were classified as subjective cognitive decline (n=37) or mild cognitive impairment (n=79). Participants underwent neurological and neuropsychological examination, and brain MRI (1.5T). The Czech version of MBI-C was administered to participants´ informants. Five a priori selected brain regions were measured: thicknesses of the orbitofrontal cortex (OFC), anterior cingulate cortex (ACC), posterior cingulate cortex (PCC) and entorhinal cortex (ERC) and volume of the hippocampus (HV), and correlated with MBI-C total and domain scores. Results: ERC was associated with MBI-C total score (rS=-.368, p<.001) and with impulse dyscontrol score (rS=-.284, p=.002). HV was associated with decreased motivation (rS =-.248, p=.008) and impulse dyscontrol score (rS=-.240, p=.011). Conclusions: NPS, particularly in the MBI impulse dyscontrol and motivation domains, are associated with medial temporal lobe atrophy in a clinical cohort of nondemented older adults. This study supports earlier involvement of temporal rather than frontal regions in NPS manifestation. Since these regions are typically affected early in the course of Alzheimer´s disease (AD), MBI-C may potentially help further identify individuals at-risk of developing AD dementia.